A proteção dos bens jurídicos como fundamento do direito penal - Godoy, Regina Maria Bueno de (2010)
The present work points out the importance and the necessary application of the theory of the juridical good in the Brazilian criminal legal system. The notion of that fundamental value and its protection form are sources in which the criminal law needs obligatorily rests its basis, although not exclusively. The subsidiary performance and the ultima ratio of that branch of the law confirms that its intervention can only happens in the hypotheses of serious lesions to those vital goods for the peaceful coexistence of the society. The theory also possesses, beside several other constitutional or criminal principles, the function of limiting the interference of the ius puniendi of the State and to guide it in the moment of the incriminating activity. The absence of the material concept of juridical good, the new panorama brought by the current conception of vagueness, the supraindividual juridical goods, as well as the critics to the adoption of the theory do not possess the privilege of moving away its obligatory observance in the national legal system